Clinical correlates of laterality among school-age children in the United States. Issue 5 (2nd September 2020) - Lu, Nancy; Rigsby, Devyn C.; Keim, Sarah A.; Rapoport, Eli; Adesman, Andrew
ABSTRACT: Researchers have long been interested in whether lateral preference is associated with giftedness, season of birth, and/or ADHD constructs (short attention span, high level of activity, and impulsivity). The objective of this study was to examine these associations in a large, longitudinal sample of U.S. children (National Collaborative Perinatal Project (CPP), 1959–1973). Children born to women in this pregnancy cohort underwent a neonatal exam and an exam at age 7 years to assess lateral preference of the hand and eye, IQ on the Wechsler Intelligence Scale for Children (WISC), and ADHD symptoms. Children with perinatal/neonatal risk factors for neurologic impairment or early signs of neurological abnormality were excluded from our analyses. The final sample included 25, 385 children. Associations between laterality and IQ were examined using linear and logistic regression models adjusted for sex, race, and socioeconomic status. Associations between laterality and ADHD symptoms and between season of birth and laterality were estimated using multivariable logistic regression. In this large, longitudinal study of neurologically healthy children, modest associations were observed between hand/eye preference and IQ and hyperactivity only.